2011
DOI: 10.1021/ma202059t
|View full text |Cite
|
Sign up to set email alerts
|

Upper Critical Solution Temperature of Poly(N-acryloyl glycinamide) in Water: A Concealed Property

Abstract: Polymers showing an upper critical solution temperature (UCST) in water are rare. Recently, the nonionic homopolymer poly(N-acryloyl glycinamide) (poly(NAGA)) has been shown to exhibit a sharp upper critical solution temperature in pure water as well as in electrolyte solution. Although poly(NAGA) is known for decades the UCST behavior had not been reported. The first controlled radical polymerization of poly(NAGA) by the RAFT (reversible addition–fragmentation transfer) process was also achieved recently, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
282
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(299 citation statements)
references
References 35 publications
8
282
0
1
Order By: Relevance
“…The heating/cooling rate was 1.0 °C/min and the inflection points were defined as cloud points. Reprinted with permission from reference [20]. Copyright (2012) American Chemical Society.…”
Section: Upper and Lower Critical Solution Temperaturementioning
confidence: 99%
“…The heating/cooling rate was 1.0 °C/min and the inflection points were defined as cloud points. Reprinted with permission from reference [20]. Copyright (2012) American Chemical Society.…”
Section: Upper and Lower Critical Solution Temperaturementioning
confidence: 99%
“…al. 4 The same group has reported several examples of the previously unnoticed UCST behaviour of well-known polymer systems such as poly(acrylamide-co-acrylonitrile) 5 and poly(N- 35 acryloyl glycinamide); 6 however few other examples exist. Polybetaines are electrically neutral polymers that contain both cationic and anionic groups within a single monomer unit.…”
Section: Introductionmentioning
confidence: 99%
“…Since this first observation and study there have been very few works further investigating the characteristics and mechanisms of complexation of NAGA as either homopolymer or co-monomer [83]. A renewed interest in 2007 in patent literature [84,85] and again in 2010 in the solution properties of single polymer chains and synthesis methods for PNAGA [30,86,87] suggests that more investigations of the characteristics and properties of NAGA-based gels may be expected in the future. The only previous work discovered to observe the thermophilic behavior of NAGA-based gels was with IPNs by Sasase et al [69].…”
Section: Stabilizing Am-aa Complexationmentioning
confidence: 99%
“…The VPTT was determined to be ~22.5 °C upon heating and ~12.3 °C upon cooling by a turbidity photometer at 670 nm at a heating rate of 1 °C min −1 . A later publication by Seuring et al investigated why thermophilic behavior for PNAGA had not been observed while it had been know to undergo thermo-reversible gelation for near half a century [87]. It was determined that any ionized groups in the polymer prevent phase separation, ionic groups can be introduced unintentionally by either "acrylate impurities in the monomer, hydrolysis of the polymer side chains, and/or usage of ionic initiators or chain transfer agents".…”
Section: Stabilizing Am-aa Complexationmentioning
confidence: 99%